Deciduous teeth caries in the population of Polish children aged 0.5-6 years - Szymańska, Jolanta; Szalewski, Leszek (Polish Journal of Public Health, 2011)
Deciduous teeth caries is a serious health problem of the children population in Poland. On the basis of a review of papers published in the Polish-language dental journals in 2004-2009, the status of deciduous dentition in Polish children was presented. The research results were compared according to the age of the studied children. Information on the caries disease was expressed by caries indices – frequency, average dmft number, dmft index and dental treatment index. The frequency of caries in 3-year-olds was ca. 45-77%, in the group of 4-year-olds – 50-66%, and with the increasing age of children, it reached ca. 57-94% in 6-year-old children. The average number of caries-affected teeth in children diagnosed with caries (dmft index) was: 2.13-5.31 in 3-year-olds, 3.79 in 4-year-olds, 4.41-4.67 in 5-year-olds, and ca. 5-6.17 in 6-year-olds. The values of dental treatment index for deciduous teeth were at the level of 0.1 in 4-year old children, 0.09-0.18 in 5-year-olds, and 0.075-0.75 in 6-year-olds. Results of the cited studies confirm that it would be extremely difficult to achieve the goal set by the World Health Organization for oral cavity health in 2015 – 60% of children free from caries. The frequency and intensity of caries processes in deciduous dentition of Polish children vary according to their age and place of residence (city/village, region of Poland), reaching high values. A considerable level of negligence in the area of children dental care is shown by low values of the deciduous teeth treatment index. It seems that the lack of far-reaching, comprehensive and planned prophylaxis and treatment of children with deciduous dentition, combined with a low health awareness of parents, are the main causes of current health status of Polish children.